A Comparison Study of Masturbating and Non masturbating Female and their Marital and Sexual Satisfaction in India - R. Vikhram Ramasubramanian; Veerabalajikumar (Archives of Medicine and Health Sciences)
Background and Aim: Sexual and marital well-being is a crucial aspect of overall happiness and fulfillment in our lives. Masturbation, on the other hand, refers to the act of self-stimulation for sexual pleasure. This study aims to find the level of marital and sexual satisfaction of the females who are masturbating and who are not masturbating. The objectives are to measure the level of marital and sexual satisfaction of women and to understand the selected sociodemographic conditions and to find out significant mean differences in subgroups (based on sociodemographic details) and masturbation with regard to marital and sexual satisfaction. Materials and Methods: A comparative study was conducted. Through simple random sampling, 120 females who were married and who can understand English were selected for the study, 60 were masturbates, and 60 were non-masturbates. The study was conducted from February 2022 to March 2023. Twenty items the new sexual satisfaction scale and 15 items the ENRICH marital satisfaction scale, and a semi-structured interview schedule was administered. Data were statistically analyzed using the Statistical Package for the Social Services software, Version 26.0. The correlation was calculated for the variables. A simple percentage analysis was used. The Pearson correlation method was used to find the relationship between the variables. A one-way ANOVA was employed to find out the significant mean difference between the demographic variables with a 95% confidence level, and P < 0.05 was considered statistically significant. Results: The result indicates that nonmasturbators have a higher mean value in both marital and sexual satisfaction. Conclusion: Nonmasturbators have higher mean value in both marital and sexual satisfaction. This study helps to create the awareness and promote masturbation, marital, and sexual satisfaction among school children.